2022
DOI: 10.1177/13591045221076889
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence and severity of psychiatric illness in hospitalized youth during COVID-19

Abstract: Background and objectives Previous studies have demonstrated an increase in mental health emergencies among youth seen in ambulatory and emergency room settings during the COVID-19 pandemic. This study investigates rates of mental health-related consultation and markers of illness severity since the start of the pandemic. Methods We evaluated all pediatric patients admitted to a single children’s hospital from March 2019 to March 2021 who received psychiatry and/or psychology consults. We report the absolute n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…This period is parallel with our study period. During the pandemic there was an increase in hospital mental health related admissions among children and adolescents [16,17]. The information on triggers for PFAPA attacks is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This period is parallel with our study period. During the pandemic there was an increase in hospital mental health related admissions among children and adolescents [16,17]. The information on triggers for PFAPA attacks is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Research that directly addresses patient and family satisfaction of telehealth provision for inpatient pediatric psychology care is also needed as little is understood about how this modality of care delivery is received by pediatric inpatients. A better understanding of the efficacy and reception of virtual care could lead to increased access to care, particularly as many hospital systems are experiencing more admissions for youth with mental health concerns which has the potential to significantly tax existing CL services (Leith et al, 2022 ; Monroe et al, 2022 ). Thus, psychologists should continue to assess the advantages and disadvantages of returning to pre-pandemic modalities of care and consider approaches that maintain or increase care to underserved populations.…”
Section: Limitationsmentioning
confidence: 99%
“…Many factors exacerbate their mental wellbeing, including quarantine, infection fear, frustration, and financial loss [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Many studies reported that teenagers were particularly affected, as quarantine caused a sudden interruption of all their social activities [ 6 , 7 , 14 , 15 ]. During lockdowns, they engaged in less physical activity, experienced irregular sleeping patterns, and followed unhealthy eating habits.…”
Section: Introductionmentioning
confidence: 99%
“…During lockdowns, they engaged in less physical activity, experienced irregular sleeping patterns, and followed unhealthy eating habits. All these lead to increased symptoms of anxiety, irritability, insomnia, and depression [ 5 , 6 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation